0966 The effects of feeding low trypsin inhibitor soybean meal to broilers on growth performance. (1st October 2016) - Hosotani, G.; Freitas, B.; Kerley, M. S.; Shannon, M. C.
Abstract: A 21-d experiment was conducted to compare soybean meal (SBM) from low trypsin inhibitor to parent soybean cultivars on growth performance of broilers. One hundred and fifty 1-d-old male broilers (Ross 308) were randomly placed in battery cages and allocated to 6 dietary treatments with 5 replicates and 5 birds per replicate in a factorial arrangement of 3 SBM sources, solvent extracted conventional SBM (SOLV), cold-pressed conventional SBM (CON), and cold-pressed low trypsin inhibitor SBM (LTI) by laboratory-scale mechanical extraction. All SBM sources were either non-heated or heated in a forced-air oven at 120°C for 20 min. Diets were formulated to meet or exceed NRC (1994 and Aviagen nutrient requirements. Broilers were weighed and feed disappearance measured on d 7, 14, and 21. Statistical analyses were performed as a randomized complete block design using PROC GLM of SAS with significance level set at P ≤ 0.05. Feeding sources of SBM resulted in differences in ADG, ADFI, and feed conversion ratio (FCR) in all measurements ( P < 0.05). Overall, chicks fed LTI had intermediate ADG (36 g; P < 0.0001) compared to CON and SOLV (30 and 50 g, respectively), and FCR (1.38 vs. 1.54, and 1.19, respectively; P < 0.0001). Chicks fed LTI or HTI had lower ADFI compared to SOLV (49, 46, and 59 g, respectively; P < 0.0001). Heating SBM improved FCR on wks 1 and 2, resulting in overall improvement from 1.40 to 1.34 FCR ( P = 0.0017). Interaction between SBM sources and heat treatment was not significant throughout the experiment. In conclusion, feeding LTI improved growth performance of broiler chicks compared to CON by 20% in ADG and 10% in FCR. We hypothesized that feeding LTI to broilers would result in similar growth performance of broilers fed SOLV. However, feeding either heated or non-heated LTI to broilers did not have similar growth performance as broilers fed SOLV, decreasing ADG by 28% and impairing FCR by 16%, most likely due to other anti-nutritional factors or nutritional characteristics that impaired growth performance of broiler chicks.